Myeloid-Derived Suppressor Cells in the Context of Allogeneic Hematopoietic Stem Cell Transplantation - D'Aveni, Maud; Notarantonio, Anne B.; Bertrand, Allan; Boulangé, Laura; Pochon, Cécile; Rubio, Marie T. (Frontiers in Immunology, 2020)
Myeloid-derived suppressor cells (MDSCs) are innate immune cells that acquire the capacity to suppress adaptive immune responses. In the context of allogeneic hematopoietic stem cell transplantation (allo-HSCT), MDSCs (in the donor graft and in the recipient, after allo-HSCT) might mediate immune suppression through multiple mechanisms. However, it remains unclear how MDSCs can be distinguished from their normal myeloid counterparts in the hematopoietic stem cell donor graft and during immune reconstitution after allo-HSCT in the recipient. Our ability to understand their exact role in allo-HSCT is limited by the absence of a specific gene signature or surface markers for identifying MDSCs among myeloid cells and by their plasticity in different microenvironments. According to various studies, MDSCs might induce transplant tolerance and control graft versus host disease (GVHD), but their impact on the graft versus tumor effect (GVT) is not fully understood. In fact, we know that MDSCs commonly expand in patients with cancer, and they are thought to promote hematological malignancy progression. However, little is known about whether depleting them might be an effective strategy for enhancing GVT effects. Here, we review data published over the past 40 years on allo-HSCT to delineate the different MDSC subsets, and their abilities to induce transplant tolerance and preserve the GVT effect. This review will provide a basis for determining whether one MDSC subset might be proposed as the most appropriate candidate for cellular therapies due to its ability to modulate GVHD.